On the volume resistivity of silica nanoparticle filled epoxy with different surface modifications. (August 2017) - Chu, Pengfei; Zhang, Hui; Zhao, Jun; Gao, Feng; Guo, Yufeng; Dang, Bin; Zhang, Zhong
Abstract: It was found that metallic oxide nanoparticles may positively influence insulation properties of polymers working under high electric field. Herewith, four kinds of surface-modified silica nanoparticles were employed to fabricate epoxy nanocomposites. The surface properties of nanoparticles were characterized by Fourier-transform infrared spectroscopy, thermogravimetric analysis and contact angles. The effects of surface modification, filler fraction and test temperature on volume resistivity ( ρ v ) of epoxy nanocomposites were studied. It was found that, at different test temperatures, the long-alkyl-modified nanoparticles resulted in higher ρ v values of epoxy and less ρ v sensitivity to temperature, compared to the short-alkyl-modified and hydroxyl-modified ones. The surface polarity of nanoparticles was found to correlate with the ρ v values well. The surface modification may cause two possible mechanisms that affect the ρ v values of the epoxy: (i) to offer the nanoparticles different levels of water absorption; (ii) to change the Maxwell-Wagner-Sillars polarization behaviors of the composites.